‘Pemikiran’ berdasarkan pameran kea rah hakikat mistik 1974 oleh Redza Piyadasa dan Sulaiman Esa - Muhamad Aifa, Suhadi (Universiti Malaysia Sarawak (UNIMAS), 2016)
This work was inspired by an exhibition entitled "Towards a Mystical Reality" in 1974, this exhibition was once again sparked polemics and controversy among the various arts people in Malaysia. Therefore, this work is a critique of the few artists in Malaysia, which is still tied up and confined in producing works of art characterized by the flow of Modernism. Thus, this work provides a strong focus on installation art than painting, sculpture and prints.